2009
DOI: 10.1086/597030
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Television-Viewing Experience through Commercial Interruptions

Abstract: Consumers prefer to watch television programs without commercials. Yet, in spite of most consumers' extensive experience with watching television, we propose that commercial interruptions can actually improve the television-viewing experience. Although consumers do not foresee it, their enjoyment diminishes over time. Commercial interruptions can disrupt this adaptation process and restore the intensity of consumers' enjoyment. Six studies demonstrate that, although people preferred to avoid commercial interru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
89
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(96 citation statements)
references
References 30 publications
5
89
0
2
Order By: Relevance
“…Our motivation for this step was to free mental resources to foster customers' systematic processing of the video. However, including the break might have introduced a satiation effect in the high ability group (Nelson, Meyvis, and Galak 2009), positively affecting perceived service performance.…”
Section: Limitationsmentioning
confidence: 99%
“…Our motivation for this step was to free mental resources to foster customers' systematic processing of the video. However, including the break might have introduced a satiation effect in the high ability group (Nelson, Meyvis, and Galak 2009), positively affecting perceived service performance.…”
Section: Limitationsmentioning
confidence: 99%
“…This happens for a variety of stimuli ranging from the primarily physiological, such as food (Rolls, van Duijvenvoorde, and Rolls 1984) and sex (O'Donohue and Geer 1985), to the primarily nonphysiological, such as music (Ratner, Kahn, and Kahneman 1999), television programs (Nelson, Meyvis, and Galak 2009), art (Berlyne 1971), homes (Hsee et al, forthcoming), and cars (Frank 1999). In fact, satiation is often cited as a primary barrier to enduring happiness since, regardless of how satisfying a stimulus might be initially, that satisfaction tends to fade with repetition (Brickman and Campbell 1971).…”
mentioning
confidence: 99%
“…However, after a short break, his/her enjoyment will increase to a level higher than immediately prior to the break. Similarly, commercials have been shown to increase the pleasure derived from a television show, by interrupting adaptation (Nelson, Meyvis, & Galak, 2009). Although these studies did not explore breaks in interpersonal relationships per se, we believe their findings are likely to generalize to romantic relationships.…”
Section: Long-distance Relationshipsmentioning
confidence: 93%
“…Although thus far we have only discussed adaptation to positive events and emotions, evidence suggests that variety of negative experiences can also impede adaptation. For example, researchers have found that people enjoy experiences with negative interruptions, such as irritating commercials or jarring noises, more than those same experiences without interruptions (Nelson & Meyvis, 2008;Nelson et al, 2009). If unhealthy relationships were negative all of the time, few people would remain in them.…”
Section: Abusive Relationshipsmentioning
confidence: 99%